KEBEBASAN BERKONTRAK DALAM KONTRAK BAKU KREDIT PERUMAHAN - Kusumastuti, Dora (Widya Wacana: Jurnal Ilmiah, 2014)
To know about the properties mortgage if it has shown realization of the freedom principle of contract and how properties mortgage can realize the freedom of contract. The freedom of contract as an important principle for validity agreement, should uphold the moral value, and in the making of a contract there are no abuse of situation, because it can revoke a contract. To realize the freedom of contract, a contract should be based on goodwill of the parties, which began from pre-contract, execution of the contract, and post-contract. Â  Â  Key Word : Freedom of contracts, standard contracts, properties contracts